Project Report on Work Force Management - ARUN KUMAR, RAJGOPAL A, SANTOSH and THOMAS CYRIAC (2005)
INTERNAL GUIDE: GOERAMMA G S, MVJCE EXTERNAL GUIDE: NIRANJAN S HIREMATH, MPHASIS TECH
Keywords: Work Force Management